Optimal location of accident relief facilities in a railway network - Tripathi G.; Tanksale A.N.; Verma M. (My University, 2025)
We study the strategic problem of optimally locating different types of relief facilities across the railway network that could respond to an accident-related emergency. A multi-objective optimization program that aims to maximize network coverage, prioritizes important rail links, optimizes redundancy, and minimizes overall response times is proposed. The concept of cooperative coverage is adopted where a decaying function is used to ascertain the coverage, and the importance of rail-links is determined based on inputs from the experts via a questionnaire-based survey. The multi-objective optimization program is solved using an interactive augmented ε-constraint method that makes use of intervention from the decision-maker. The proposed optimization program is used to study the North Central Railway zone of Indian Railways, and the computational experiments demonstrate that reconfiguring the existing network of relief facilities will increase the coverage of rail nodes by 7.86% and that of rail-links by 10.78%. © 2021 Elsevier Ltd